IMPROVING ECONOMIC EFFICIENCY OF ENTERPRISES IN MODERN CONDITIONS - Abdusamatova Aziza (Ecominds Press, 2025)
This article examines the theoretical foundations and practical approaches to improving the economic efficiency of enterprises under modern economic conditions. The study highlights the crucial role of innovation, digital transformation, human capital development, and effective management in enhancing enterprise performance and competitiveness. The article analyzes the internal and external factors that influence efficiency, including resource utilization, technological progress, market competition, and investment strategies. It is emphasized that economic efficiency is not limited to reducing production costs but also involves optimizing management systems, increasing labor productivity, and promoting innovation-based growth. Using analytical and comparative methods, the research reviews international experiences of European and Asian enterprises in implementing efficiency-enhancing practices. The findings show that enterprises that invest in digital technologies and employee training can achieve a 15–20% improvement in performance. Moreover, foreign investment and open competition contribute to industrial modernization and sustainable growth. The study concludes that improving economic efficiency requires a comprehensive approach, combining innovation, financial management, and human resource strategies. This approach not only increases productivity and profitability but also strengthens the long-term stability of enterprises in a rapidly changing global market. The results of this study can serve as a scientific basis for further research and practical recommendations in enterprise management and economic policy development.